Development and Internal Validation of Supervised Machine Learning Algorithm for Predicting the Risk of Recollapse Following Minimally Invasive Kyphoplasty in Osteoporotic Vertebral Compression Fractures - Dong, Sheng-tao; Zhu, Jieyang; Yang, Hua; Huang, Guangyi; Zhao, Chenning; Yuan, Bo (Frontiers in Public Health, 2022)
Background: The published literatures indicate that patients with osteoporotic vertebral compression fractures (OVCFs) benefit significantly from percutaneous kyphoplasty (PKP), but this surgical technique is associated with frequent postoperative recollapse, a complication that severely limits long-term postoperative functional recovery. Methods: This study retrospectively analyzed single-segment OVCFs patients who underwent bilateral PKP at our academic center from January 1, 2017 to September 30, 2019. Patients were assigned to recollapse group and non-recollapse group, defined as whether sagittal anterior vertebral height is lost more than 10% compared to postoperative radiographs during follow-up. Univariate and multivariate logistic regression analyses were performed to determine the risk factors affecting recollapse after PKP. Based on the logistic regression results, we constructed one support vector machine (SVM) classifier to predict recollapse using machine learning (ML) algorithm. The predictive performance of this prediction model was validated by the receiver operating characteristic (ROC) curve, 10-fold cross validation and confusion matrix. Results: Among the 346 consecutive patients (346 vertebral bodies in total), postoperative recollapse was observed in 40 patients (11.56%). The results of the multivariate logistical regression analysis showed that high BMI (OR 2.08, 95% CI 1.58-2.72, p<0.001), low BMD T-scores (OR 4.27, 95% CI 1.55-11.75, p=0.005), presence of IVC (OR 3.10, 95% CI 1.21-7.99, p=0.019), separated cement masses(OR 3.10, 95% CI 1.21-7.99, p=0.019), cranial endplate or anterior cortical wall violation (OR 0.17, 95% CI 0.04-0.79, p=0.024), cement-contacted upper endplate alone (OR 4.39, 95% CI 1.20-16.08, p=0.025), thoracolumbar fracture (OR 6.17, 95% CI 1.04-36.71, p=0.045) were identified as independent risk factors for recollapse after a kyphoplasty surgery. Furthermore, the evaluation indices demonstrated a superior predictive performance of the constructed SVM model, including mean AUC 0.81, maximum AUC 0.85, accuracy 0.81, precision was 0.89 and sensitivity 0.98. Conclusions: For patients with OVCFs, the risk factors leading to postoperative recollapse were multidimensional. The predictive model we constructed provided insights into treatment strategies targeting for secondary recollapse prevention.